Arginylation Regulates Intracellular Actin Polymer Level by Modulating Actin Properties and Binding of Capping and Severing Proteins - Saha, Sougata (The American Society for Cell Biology, 2010)
Actin arginylation regulates lamella formation in motile fibroblasts, but the underlying molecular mechanisms are unknown. To understand how arginylation affects the actin cytoskeleton, we investigated the biochemical properties and the structural organization of actin filaments in wild-type and arginyltransferase (Ate1) knockout cells. We found that Ate1 knockout results in a dramatic reduction of the actin polymer levels in vivo accompanied by a corresponding increase in the monomer level. Purified nonarginylated actin has altered polymerization properties, and actin filaments from Ate1 knockout cells show altered interactions with several associated proteins. Ate1 knockout cells have severe impairment of cytoskeletal organization throughout the cell. Thus, arginylation regulates the ability of actin to form filaments in the whole cell rather than preventing the collapse of preformed actin networks at the cell leading edge as proposed in our previous model. This regulation is achieved through interconnected mechanisms that involve actin polymerization per se and through binding of actin-associated proteins.